The Influence of Transformational Leadership on Performance Through Motivation and Job Satisfaction for Teachers at Yayasan Pendidikan Al-Istiqomah Karya Guna Kebumen - Muhamad Samsul Jamaludin; Corry Yohana; Osly Usman (International Journal of Economics, Management and Accounting (IJEMA), 2024)
In facing complex global dynamism, a dynamic organization must be able to overcome real challenges from all aspects to produce superior and competitive performance. This research aims to determine the influence of transformational leadership on the performance of teachers at Yayasan Pendidikan Al-Istiqomah Karya Guna Kebumen through motivation and job satisfaction as intervening variables. Data collection techniques using questionnaires, observation and literature study. This type of research is quantitative research and data analysis is carried out using Partial Least Square with SmartPLS 4.0 software. The results of this research show; 1. Transformational Leadership has a positive and significant effect on motivation directly, 2. Transformational Leadership has a positive and significant effect on job satisfaction directly, 3. Transformational leadership has a negative and insignificant effect on performance, 4. Motivation has a negative and insignificant effect on performance, 5. Job satisfaction has a positive and significant effect on performance directly, 6. Transformational leadership has a negative and insignificant effect on performance which is mediated through motivation, 7. Transformational leadership has a positive and significant effect on performance which is mediated through job satisfaction.